Effect of 5-bromodeoxyuridine on vaccinia virus-induced polypeptide synthesis: selective inhibition of the synthesis of some post-replicative polypeptides. - Pennington, T H (1976)
The effect of 5-bromodeoxyuridine (BrdU) on vaccinia virus-induced polypeptide synthesis in BSC-1 cells has been investigated. Most virus-induced pre- and post-replicative polypeptides were synthesized in concentrations of 5-bromodeoxyuridine that inhibited virus growth. The synthesis of a few post-replicative polypeptides, however, was severely inhibited under these conditions; included in this group was the precursor of a major core component, polypeptide P4b. A delay in the switch-off of pre-replicative polypeptide synthesis and in the onset of post-replicative polypeptide synthesis was also observed. The significance of these observations is discussed.